Towards a new monolingual Hungarian explanatory dictionary: overview of the hungarian explanatory dictionaries - Veronika Lipp; László Simon (Studia Lexicographica)
The Lexical Knowledge Representation Research Group at the Department of Lexicology is one of the youngest research groups of the Hungarian Research Centre for Linguistics, founded in February 2020. The group is currently working on a new version of a monolingual explanatory dictionary partly based on The Explanatory Dictionary of the Hungarian Language. The aim is to compile an up-to-date online dictionary of contemporary Hungarian (2001–2020) by corpus-driven methods.